2011
DOI: 10.3386/w17367
|View full text |Cite
|
Sign up to set email alerts
|

Trading and Enforcing Patent Rights

Abstract: We would like to thank two anonymous referees and the Editor for very constructive comments on an earlier version of the paper. We are also grateful to Victor Aguirregabiria, Ashish Arora, Pierre Azoulay, Christian Catalini, Dietmar Harhoff, Nico Lacetera, Josh Lerner, Megan MacGarvie, Matt Mitchell, Jeff Thurk, Dan Trefler and Heidi Williams for comments and suggestions on earlier drafts, and to Grid Thoma for helping with the matching algorithm. We also thank seminar and conference participants at Berkeley, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In this context, a firm's patent portfolio can be leveraged as a bargaining chip in order to deal with potential patent hold-up problems and force competitors into negotiations (Cohen et al, 2000;Hall and Ziedonis, 2001). In this sense, several studies have documented that patented inventions of firms with larger patent portfolios are less likely to be involved in patent litigation cases (Lanjouw and Shankerman, 2004;Galasso et al, 2013). For such reasons, we advance the following hypothesis: Hypothesis 2.…”
Section: Perceived Litigation Risks and Post-ipo Innovative Productivitymentioning
confidence: 90%
“…In this context, a firm's patent portfolio can be leveraged as a bargaining chip in order to deal with potential patent hold-up problems and force competitors into negotiations (Cohen et al, 2000;Hall and Ziedonis, 2001). In this sense, several studies have documented that patented inventions of firms with larger patent portfolios are less likely to be involved in patent litigation cases (Lanjouw and Shankerman, 2004;Galasso et al, 2013). For such reasons, we advance the following hypothesis: Hypothesis 2.…”
Section: Perceived Litigation Risks and Post-ipo Innovative Productivitymentioning
confidence: 90%
“…Specific studies on the relationship among patent age and selling price have been conducted (Vimalnath et al, 2017), but they are still limited, too (Kim & Lee, 2019). A higher, but still limited, quota of studies is focused on patent auctions (Caviggioli & Ughetto, 2013;Fischer & Leidinger, 2014;Odasso et al, 2015;Piirainen, Andersen & Andersen, 2013;Sneed & Johnson, 2009;Sreekumaran Nair et al, 2011;Vimalnath et al, 2017) and reassignments (Caviggioli et al, 2017;Drivas & Economidou, 2015;Figueroa & Serrano, 2013;Galasso et al, 2013;Serrano, 2010). In detail, only Drivas and Economidou, (2015) investigate on the geographic aspects related to knowledge flows, but they focus on cross-organizational patent acquisitions within the U.S. only.…”
Section: Literature Review and Motivationmentioning
confidence: 99%
“…Current statistics on international and domestic IP trade may be partly explained by the relative advantages of setting up separate companies and vehicles for managing revenues arising from the use of IP. 20 Recent academic research has for example demonstrated that differences in capital gains taxes that apply to patent sales can drive incentives for individual inventors to sell their patents (Galasso et al, 2011). This allows the researchers to infer that markets in which patents are more likely to be traded will benefit from reduced litigation due to comparative advantage among sellers in patent enforcement.…”
Section: Ip Regime Features and Enforcementmentioning
confidence: 99%